Inventor Returns and Mobility - Dietmar Harhoff; David Heller; Paul P. Momtaz (CESifo GmbH, 2024)
We show that firm and industry, rather than inventor and invention factors, explain more than half of the variation in inventor returns in administrative employer-inventor-patent-linked data from Germany. Between-firm variation in inventive rents is strongly associated with inventor mobility. Inventors are more likely to make a move just before a patent is filed than shortly thereafter and benefit from their move through a mobility-related marginal inventor return. Employers that pay inventor returns in excess of the expected return gain a favorable position in the market for inventive labor with subsequent increases in patent quality and quantity. Consistent with theoretical arguments, effect sizes also depend on employer-inventor technological complementarity, degree of competition, and invention quality.
Keywords: O31; J24; J62; 330; inventor returns; labor mobility; patents; inventive productivity